THE INFLUENCE OF DAKWAH USING MEMES ON INSTAGRAM SOCIAL MEDIA ON THE FAITH OF ISLAMIC NETIZENS IN INDONESIA - Muhamad Fadhly Rafiansyah (Indonesian Journal of Islamic Communication, 2023)
Abstrac: This study explores the influence of dakwah memes on the faith of Islamic netizens in Indonesia. Through an analysis of various dakwah memes found on social media platforms, particularly Instagram, and examining the responses and interactions of users, this research aims to elucidate the impact of memes on religious beliefs. The methodology involves observation and documentation of memes disseminated by the Instagram account, coupled with an analysis of comments and engagements from users. The findings indicate that dakwah memes play a significant role in strengthening the faith of Islamic netizens by delivering religious messages in a creative and engaging format. Additionally, the inclusivity and viral nature of memes contribute to their effectiveness in reaching a diverse audience, including those less engaged in religious practices. Consequently, dakwah memes serve as a powerful tool for promoting religious teachings and fostering a sense of community among Muslims in the digital age.